Novel PKLR missense mutation (A300P) causing pyruvate kinase deficiency in an Omani Kindred—PK deficiency masquerading as congenital dyserythropoietic anemia. Issue 2 (7th February 2022) - Fawaz, Naglaa; Beshlawi, Ismail; Alqasim, Alauldeen; Zachariah, Mathew; Russo, Roberta; Andolfo, Immacolata; Gambale, Antonella; Pathare, Anil; Iolascon, Achille
Abstract: We report herein a child with transfusion‐dependent chronic anemia, the cause of which was difficult to establish because of his transfusion dependency. The clinical and laboratory features suggested a chronic nonspherocytic hemolytic anemia (CNSHA) with bone marrow features suggestive of congenital dyserythropoietic anemia (CDA). DNA studies, however, revealed the underlying condition to be due to a novel mutation in the PKLR gene responsible for pyruvate kinase deficiency (PKD). Molecular investigations by a targeted next‐generation sequencing (t‐NGS) using a custom panel of 71 genes involved in the red blood cell (RBC) disorders revealed that the patient was homozygous for a novel missense mutation c.898G>C, p.Ala300Pro, whereas both his parents were heterozygous for the same mutation. Abstract : Pyruvate kinase deficiency (PKD) is the most common enzyme defect of glycolysis and an important cause of hereditary, nonspherocytic hemolytic anemia. The disease has a worldwide geographical distribution but there are no verified data regarding its frequency, although it impacts patient's health‐related quality of life. Difficulties in the diagnostic workflow and interpretation of PK enzyme assay likely play a role. Reporting cases may be helpful to increase the awareness in PKD.